Financing Green Urban Infrastructure - Merk, Olaf (OECD Publishing, 2012)
This paper presents an overview of practices and challenges related to financing green sustainable cities. Cities are essential actors in stimulating green infrastructure; and urban finance is one of the promising ways in which this can be achieved. Cities are key investors in infrastructure with green potential, such as buildings, transport, water and waste. Their main revenue sources, such as property taxes, transport fees and other charges, are based on these same sectors; cities thus have great potential to ?green? their financial instruments. At the same time, increased public constraints call for a mobilisation of new sources of finance and partnerships with the private sector. This working paper analyses several of these sources: public-private partnerships, tax-increment financing, development charges, value-capture taxes, loans, bonds and carbon finance. The challenge in mobilising these instruments is to design them in a green way, while building capacity to engage in real co-operative and flexible arrangements with the private sector
Keywords: Urban, Rural and Regional Development